2005
DOI: 10.1111/j.1600-0714.2005.00319.x
|View full text |Cite
|
Sign up to set email alerts
|

Palatine tonsils in smoker and non‐smoker patients: a pilot clinicopathological and ultrastructural study

Abstract: These preliminary results suggest a possible interference of cigarette smoking with the therapy response as well as a possible role of tobacco smoke in impairment of inflammatory response. Results are critically analysed and discussed. Literature data on this subject are reviewed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 24 publications
1
8
1
Order By: Relevance
“…No patient of our patient population had presented with a bilateral PTA, while others reported rates ranging between 0.8 and 4.9 % [27,30,[32][33][34]. In accordance with most studies [6,[35][36][37][38][39][40][41][42][43] smoking habits were overrepresented (43.8 %) in our patient population. In contrast to other studies, none of our patients had presented with a concomitant infectious mononucleosis [11,[44][45][46] or Kawasaki's disease [37,[44][45][46][47][48][49][50][51][52].…”
Section: Discussionsupporting
confidence: 93%
“…No patient of our patient population had presented with a bilateral PTA, while others reported rates ranging between 0.8 and 4.9 % [27,30,[32][33][34]. In accordance with most studies [6,[35][36][37][38][39][40][41][42][43] smoking habits were overrepresented (43.8 %) in our patient population. In contrast to other studies, none of our patients had presented with a concomitant infectious mononucleosis [11,[44][45][46] or Kawasaki's disease [37,[44][45][46][47][48][49][50][51][52].…”
Section: Discussionsupporting
confidence: 93%
“…Smokers and non-smokers with chronic tonsillitis were compared and a longer history of recurrent tonsillitis and marked morphological changes were identified in smokers. [17] In our study, sore throat due to tonsillitis and pharyngitis was found to be lower in ex-smokers, whereas there was no difference in smokers.…”
Section: Discussioncontrasting
confidence: 43%
“…Histopathologically, smoking causes cellular and structural alterations in tonsils, leading to an increased oral acquisition of HPV [36]. This has been corroborated clinically as researchers have observed a high prevalence of HPV infection in smokers, particularly current smokers [37].…”
Section: Discussionmentioning
confidence: 97%